The COVID-19 “First Lockdown” Experience in Italy: The Role of Hope and Optimism and Their Impact on Psychological Well-Being and Risk Perception - Biassoni, Federica; Salducco, Alice; Abati, Daniela (European Journal of Mental Health, 2022)
Introduction: The present study investigates the lockdown experience in Italy during the COVID-19 pandemic within a positive psychology framework, focusing on the protective role of the positive anticipatory states: optimism and hope.Aims: The aims were to verify if and how optimism and hope influenced people’s psychological wellbeing and their risk perception of the situation, addressing how individuals portrayed the present and how they imagined the future after the lockdown.Method: Based on the differences between the two constructs, as from the literature, the hypothesis is that individuals with higher levels of optimism would report positive but hazy future scenarios and lower levels of risk perception about the future. Therefore 1,471 participants received an online survey, which was administered as a set of questionnaires investigating three areas: demographic information, psychological wellbeing, and risk of contagion perception.Results: The results showed that positive anticipatory states are positively associated with psychological wellbeing. Moreover, the results highlighted the relationship between optimism and risk perception regarding future scenarios.Conclusions: The presented predictive model demonstrated that positive anticipatory states, sex, and age had a central role in determining the psychological wellbeing during the first wave of the pandemic events in Italy. Practical implications are discussed.